Contradiction Between Law and Sub-Rules With Psychological Consideration - Shklyar, Tatiana L. (2020)
In this article authors suggest to consider features of hybrid reality, both in psychology, and in law. Authors investigate opportunities and dangers of the virtual world. Reveal the main psychological aspects provoking the person to plunge into Internet space. Also in article the main tendencies and the directions of transformation of the modern legislation connected with need to provide a condition of information security for the individual, societies, and the states in general are shown, difficulties of implementation of legal regulation and administrative control in digital space are analyzed, and the appeal of the virtual world to inhabitants, including, and in connection with his weak accountability from is at the same time proved out of.